1990
DOI: 10.1200/jco.1990.8.12.2040
|View full text |Cite
|
Sign up to set email alerts
|

Node-negative breast cancer: prognostic subgroups defined by tumor size and flow cytometry.

Abstract: Adjuvant systemic therapy for women with node-negative breast cancer is most easily justified for those patients at highest risk of relapse. We have examined the impact of tumor size, histologic grade, estrogen receptor (ER) status, tumor ploidy, and S-phase fraction (SPF) on relapse-free survival (RFS) for 169 patients with node-negative breast cancer in order to identify groups of patients at high and low risk of relapse. Patients with small tumors (less than or equal to 1.0 cm) had a significantly better RF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
50
3
4

Year Published

1991
1991
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(64 citation statements)
references
References 10 publications
7
50
3
4
Order By: Relevance
“…Does a low SPF alone identify node-negative patients at low risk? In other studies of early breast cancer, tumour size has been taken into account in addition to SPF (O'Reilly et al, 1990a;Sigurdsson et al, 1990). In the present study of young patients, however, tumour size showed no additional value, which may be due to its correlation with SPF (Table I).…”
Section: Resultscontrasting
confidence: 48%
“…Does a low SPF alone identify node-negative patients at low risk? In other studies of early breast cancer, tumour size has been taken into account in addition to SPF (O'Reilly et al, 1990a;Sigurdsson et al, 1990). In the present study of young patients, however, tumour size showed no additional value, which may be due to its correlation with SPF (Table I).…”
Section: Resultscontrasting
confidence: 48%
“…In the literature there are conflicting reports about the importance of ploidy in breast cancer. Some authors saw significantly worse survival in patients with aneuploid tumours (Kallioniemi et 1995), while others felt that ploidy did not yield additional prognostic information on survival (O'Reilly et al, 1990;Sigurdsson et al, 1990). Both MIB1-PR and SPF were significant prognostic factors for DFS in our univariate analysis.…”
Section: Discussionmentioning
confidence: 63%
“…The higher prognostic value of SPF compared to Ki-67 might be due to the longer follow up time (median 8 years). The SPF value is also higher in aneuploid tumours than in diploid tumours (O'Reilly, et al, 1990) which might give SPF a better discriminatory power than Ki-67. On the other hand, the Ki-67 scores are much higher in aneuploid carcinomas than in diploid ones (Gasparini et al, 1991).…”
Section: Discussionmentioning
confidence: 93%
“…In stage II tumours, including also node negative patients, there was a significant difference in disease free survival between Ki-67 positive/ER negative and ER positive/Ki-67 negative (P <0.005). O'Reilly has described an even more specific subdivision of patients with different prognosis using the S-phase fraction (SPF) and tumour size (O'Reilly et al, 1990). According to these results patients with tumour greater than 1 cm with an SPF < 10% have a 5-year relapse-free survival of 78%, compared to 52% in tumours of the same size with an SPF> 10%.…”
Section: Discussionmentioning
confidence: 99%